Sundanese Swear Words in Reza Auditore’s YouTube Videos: A Sociolinguistic Study - Dara, I Putu Kordiawan Bayu; Paramarta, I Made Suta; Ramendra, Dewa Putu (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
Language plays a crucial role in reflecting social identity and interaction, particularly in digital communication contexts. This study investigates the use of Sundanese swear words in Reza Auditore’s YouTube videos from a sociolinguistic perspective. While previous studies have primarily focused on swear words in face-to-face communication, limited attention has been given to their use in online media. Therefore, this research aims to identify the types, functions, and social factors influencing the use of swear words in digital discourse. This study employed a descriptive qualitative design using a case study approach. The data were collected from nine selected YouTube videos through observation and note-taking techniques. The analysis followed Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings revealed twelve Sundanese swear words categorized into four types: intelligence-based, animal-related, sexist, and racist terms. Among these, intelligence-based swear words were the most frequently used. In terms of function, swear words served four main purposes: emotional expression, abusive expression, social bonding, and attention-getting, with emotional expression being the most dominant. Furthermore, the use of swear words was influenced by four social factors: social context and environment, social relationships and intimacy, emotional expression and stress, and media and popular culture. The findings suggest that swear words in digital communication are not merely offensive but function as expressive and relational tools that contribute to audience engagement and identity construction. This study highlights the dynamic role of language in online environments and provides insights into sociolinguistic practices in digital media.